Effects of Phytohormone Compatibility on Callus Growth of Rosa rugosa tunb. Issue 3 (February 2020) - Chang, Wenbo; Wang, Xue; Lan, Ying; Wang, Meini; Wen, Bin; Li, Lan
Abstract: To obtain superior quality callus and to regenerate root system of Rosa rugosa tunb and improve culture efficiency, this experiment used a multi-factor orthogonal test method to establish a sterile system with young leaves of R. rugosa tunb as experimental materialsand different concentrations of hormones in each stage. Explore the effects of plant callus growth. The results showed that the optimal disinfection method of explants was 70% alcohol 30s+0.1% HgCl2 8min. At this time, the browning rate was 46.70%, and the infection rate was 10.00%, which was 14.40% and 72.67% lower than that before disinfection. [Primary medium]: MS+1.5 mg/L 6-BA+3.0 mg/L NAA+3% sucrose+0.9% agar, the induction rate at this time is 75.00%, an increase of 62.50% compared with no added hormone. [Proliferation medium] MS+2.0mg/L 6-BA+0.2mg/L NAA+3% sucrose+0.9% agar, the callus diameter reached 2.49cm after proliferation, the growth was strong, and the callus was highly available. [Rooting medium] MS+0.4mg/L IBA+0.5g/L AC+3% sucrose+ 0.9% agar, the rooting rate is 75.00%, the root system is long and the growth is robust.